2018
DOI: 10.1080/17430437.2018.1504776
|View full text |Cite
|
Sign up to set email alerts
|

Para-adventure: a hyper-dynamic problem for the inclusive coach

Abstract: Recent research has recognized sports coaching as complex, chaotic, and cognitively taxing for coaches. Against this backdrop, the present paper explores challenges faced by high-level coaches working with disabled performers. Specifically, it seeks to understand how coaches create mental models of performance in adventure sports and para-canoe. Five coaches were purposively sampled and underwent a semi-structured interview. A thematic analysis revealed conceptualizing the mental model as being mechanically-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Outdoor instructors work in dynamic environments (Collins and Collins 2016b;Collins, Simon, and Carson, 2018) and encounter situations brought about by the synergy of complex tasks, dynamic environments, and objectives to develop the individual Collins 2016a, 2016b). Capable instructors must manage challenges and demonstrate a pedagogical and technical agility to meet each novel issue as it arises or, ideally, through anticipating and countering that issue.…”
Section: Introductionmentioning
confidence: 99%
“…Outdoor instructors work in dynamic environments (Collins and Collins 2016b;Collins, Simon, and Carson, 2018) and encounter situations brought about by the synergy of complex tasks, dynamic environments, and objectives to develop the individual Collins 2016a, 2016b). Capable instructors must manage challenges and demonstrate a pedagogical and technical agility to meet each novel issue as it arises or, ideally, through anticipating and countering that issue.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the hyperdynamic environment, time pressure and poor information, that characterises the outdoors (L. Collins, Simon, & Carson, 2018) lends itself to a naturalistic decision-making approach (Zsambok & Klein, 1997), whereby conditions frequently involve high stakes, time pressures, uncertainty, organisational constraints and changing conditions. These factors require the decision maker to rely on experience, and intuition gained from decades of professional practice (Orasanu & Connolly, 1993;Zsambok & Klein, 1997).…”
Section: Judgement and Decision Making In The Outdoorsmentioning
confidence: 99%
“…As a final part of the interview process, the participants were asked to imagine the problems an inexperienced coach may encounter when teaching lead climbing for the first time. The participating experts identified that the key challenges existed in stages one and four of the task diagram but the impact was apparent throughout the processa 'messy' (Collins, Simon and Carson 2019) problem of multiple inter-relating factors.…”
Section: Simulation Interviewmentioning
confidence: 99%
“…The seventh interviewee described the outcome as 'paralysis by analysis'. In stages one and four, several interrelated factors such as situational awareness, sufficient practical, technical and pedagogical options, knowledge of factors that instigate needs for a change in approach and an acceptance of the need to be adaptable all coalesce in this coaching mess (Collins, Simon and Carson 2019). The fith interviewee suggested that 'just having the options isn't enough, the coach has to know why'…”
Section: Simulation Interviewmentioning
confidence: 99%